Dzień Spółdzielczości w Starogardzie. (Starogard : [s.n.], 1948)
Afisz inf. o uroczystościach 03.07.1948 r.
Keywords: Spółdzielnie -- Polska -- Starogard Gdański -- 1945-1970 -- druki ulotne; Starogard Gdański (Polska) -- 1945-1970 -- druki ulotne